2022
DOI: 10.3389/fmolb.2021.793493
|View full text |Cite
|
Sign up to set email alerts
|

MIR100HG Regulates CALD1 Gene Expression by Targeting miR-142-5p to Affect the Progression of Bladder Cancer Cells in vitro, as Revealed by Transcriptome Sequencing

Abstract: Background/Aim: The role of long non-coding RNA (lncRNA) and competing endogenous RNAs (ceRNA) networks in bladder cancer, especially the function of lncRNA-miRNA-mRNA regulatory network in bladder cancer, are still relatively poorly understood. This research mainly used transcriptome sequencing to screen key lncRNAs and ceRNAs, explore their pathogenic mechanism in bladder cancer, and search for potential diagnostic and therapeutic targets.Methods: High-throughput transcriptome sequencing, combined with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Ying W et al found that MIR100HG is lowly expressed in BC, and the overexpression of MIR100HG inhibits the proliferation and invasion of BC cells (Ying et al, 2021). Conversely, it had been reported from Zhang S's study that the overexpression of MIR100HG effectively promoted the proliferation, migration, and invasion of BC cells, and it was proved to be an independent prognostic factor for BC (Zhang et al, 2021). Our results suggested that MIR100HG was lowly expressed in PCa and indicated that this lncRNA might play a tumor-suppressive role in PCa.…”
Section: Discussioncontrasting
confidence: 52%
“…Ying W et al found that MIR100HG is lowly expressed in BC, and the overexpression of MIR100HG inhibits the proliferation and invasion of BC cells (Ying et al, 2021). Conversely, it had been reported from Zhang S's study that the overexpression of MIR100HG effectively promoted the proliferation, migration, and invasion of BC cells, and it was proved to be an independent prognostic factor for BC (Zhang et al, 2021). Our results suggested that MIR100HG was lowly expressed in PCa and indicated that this lncRNA might play a tumor-suppressive role in PCa.…”
Section: Discussioncontrasting
confidence: 52%
“…Wang et al (48) conducted a comprehensive analysis of mRNA, lncRNAs, and miRNAs between MIBC and non-tumor bladder samples based on the TCGA database and found that MIR100HG was significantly differentially expressed between MIBC and normal samples and was downregulated in MIBC. On the contrary, Zhang et al (49) found that MIR100HG was significantly up-regulated in BC tissues in comparison to adjacent tissues, and its high expression was positively correlated with the histological grade and clinical stage of BC. Besides, the expression of MIR100HG was negatively related to the OS of patients (50).…”
Section: Bladder Cancermentioning
confidence: 89%
“…Additionally, overexpression of MIR100HG inhibits tumor formation in nude mice in vivo. However, Zhang et al (49) found that high expression of MIR100HG significantly enhanced the proliferation, migration, and invasion abilities of BC cells. Taken together, these findings suggested that MIR100HG may play a vital role in BC and more studies should be replicated for the controversial results to validate the specificity and sensitivity of the MIR100HG product or individual MIR100HG as biomarkers.…”
Section: Bladder Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…MIR100HG inhibits the expression of miR-142-5p, which targets CALD1, thus relieving CALD1 from this inhibitory effect. Consequently, upregulated CALD1 results in the induction of aggressive features in bladder cancer cells[ 55 ].…”
Section: Role Of Cad In Other Cancer Typesmentioning
confidence: 99%